IJAR 2020
DOI: 10.36106/ijar/1707526
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Problems Among Adolescents:a Comparison Between Urban and Rural High School Students of Dehradun

Abstract: Introduction:- Adolescence is the transitional stage of development between childhood and adulthood. Hall denoted this period as “Storm and Stress” and states “conflict at this developmental stage is normal” leading to psychosocial problems. This study is conducted to compare the psychosocial problems between adolescents in urban and rural area. Material and methods:- A Cross-sectional study was done in November 2018 in rural and urban schools of Dehradun. Data was collected through a structured questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…11.2% and 40.7% respectively. 17,9 Also study conducted by Banstola et al revealed prevalence of psychosocial problem as 21.7% in their study. 7 In present study, psychosocial problems were more in age group of 14-16 years (39.69%) followed by 10- disorder was found to be maximum in late adolescent boys and mid adolescent girls.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…11.2% and 40.7% respectively. 17,9 Also study conducted by Banstola et al revealed prevalence of psychosocial problem as 21.7% in their study. 7 In present study, psychosocial problems were more in age group of 14-16 years (39.69%) followed by 10- disorder was found to be maximum in late adolescent boys and mid adolescent girls.…”
Section: Discussionmentioning
confidence: 79%
“…Table 1 i.e. distribution of study subjects according to their age in years shows that majority 131 (39.70%) study subjects were from age group of 14-16 years followed by 10-13 years (32.73%) and [17][18][19] Majority of study subjects belonged to nuclear family (89.93%) followed by three generation (10.32%) and rest were from joint family (05.75%) (Figure 2). Socioeconomic status was classified according to Modified Kuppuswamy socioeconomic status scale updated for the year 2021.…”
Section: Resultsmentioning
confidence: 99%